UV-transmitting step-index fluorophosphate glass fiber fabricated by the crucible technique - Galleani, Gustavo [UNESP]; Ledemi, Yannick; de Lima Filho, Elton Soares; Morency, Steeve; Delaizir, Gaëlle; Chenu, Sébastien; Duclere, Jean René; Messaddeq, Younes (Elsevier, 2017)
In this study, we report on the fabrication process of highly pure step-index fluorophosphate glass optical fibers by a modified crucible technique. High-purity fluorophosphate glasses based on 10 mol% of barium metaphosphate and 90 mol% of metal fluorides (AlF3[sbnd]CaF2[sbnd]MgF2[sbnd]SrF2) have been studied in order to produce step-index optical fibers transmitting in the deep-ultraviolet (DUV) region. The characteristic temperatures, viscosity around softening temperature and optical transmission in the UV–visible region of the prepared bulk glasses were characterized in a first step. The selected glass compositions were then used to prepare core-cladding optical preforms by using a modified built-in casting technique. While uncontrolled crystallization of the fiber was observed during the preform stretching by using the conventional method, we successfully obtained crystal-free fiber by using a modified crucible technique. In this alternative approach, the produced core-cladding preforms were inserted into a home-designed fused silica crucible assembly and heated at 643 °C to allow glass flowing throughout the crucible, preventing the formation of crystals. Single index fluorophosphate glass fibers were fabricated following the same process as well. The optical attenuation at 244 nm and in the interval 350–1750 nm was measured on both single index and step-index optical fibers. Their potential for using in DUV applications is discussed.
Keywords: Crucible method; Fibers; Fluorophosphate; Glass; UV transmitting materials